Analysis of Virtual Chat Bots in Disseminating Pornographic Content via Telegram's Anonymous Chat Feature - Marlina, Rima; Yuliana, Nina (SEAN Institute, 2024)
Telegram's Anonymouse Chat Bot allows users to exchange messages in chat rooms with purposes ranging from finding new friends, discussion forums or venting to finding a partner. This phenomenon becomes a problem when the anonymous chat feature is used by certain individuals to distribute pornographic content which can disturb other users. This research aims to analyze behavioral patterns based on the motives and objectives of using the Anonymouse Chat Bot Telegram and observe how acts of abuse can occur in this Bot. This research uses a qualitative approach with descriptive qualitative research characteristics. The results obtained from the research show that the use of Telegram's Anonymouse Chat Bot is used as a medium for establishing, searching for, adding new friends and even as a promotional medium for taking commercial advantage. Researchers see negative behavior from several individuals who distribute pornographic content due to the anonymous policy in this bot so that they are free and not responsible for what they send, whether in the form of chats, photos or videos that contain pornographic elements. Likewise, other users feel disturbed by the presence of these individuals.